ROOTING OF INDOLE-3-BUTYRIC ACID-TREATED CUTTINGS OF NINE Vitis rotundifolia CULTIVARS PERFORMED DURING SPRING AND SUMMER - DENEGA, Sérgio; BIASI, Luiz Antonio; ZANETTE, Flávio; NASCIMENTO, Ildon Rodrigues do; BLASKEVICZ, Sirlei Janine (Scientia Agraria, 2009)
The goal of this experiment was to evaluate rooting on cuttings of nine Vitis rotundifolia cultivars treated with four indole-3-butyric acid (IBA) concentrations (0, 500, 1000 and 2000 mg dm-3) in the spring and summer of 2006. A completely random design with nine treatments, 10 cuttings per parcel and four replications was used in both seasons, separately. Cuttings of Topsail, Magnolia, Creek, Noble, Roanoke, Magoon, Regale, Bontiful and Dixie were placed under intermittent mist. Both experiments were evaluated 75 days after implantation being the following variables evaluated: percentage of cuttings having leaf retention; percentage of dead cuttings; percentage of rooted cuttings; number of primary roots per cutting; average length of primary roots per cutting (cm), fresh and dry matter of roots per cutting (mg). In the summer, the greatest percentages of cuttings retaining their leaves were the non-IBA-treated ones. The percentage of dead cuttings increased however the length of roots was inversely related to IBA concentration. In the spring, the percentage of cuttings retaining leaves and percentage of rooted cuttings were inversely related to IBA concentration, the percentage of dead cuttings and fresh matter of roots increased, but with 2000 mg dm-3 the fresh matter diminished abruptly. It was possible to conclude that IBA did not improve rooting of the cuttings as it diminished rooting in many of the cultivars tested herein and its application it is not recommended for cutting propagation of Vitis rotundifolia.